2007
DOI: 10.1002/cbf.1419
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of IL‐10, IL‐6, IFN‐γ, TNF‐α and TGF‐β gene polymorphisms among Turkish lung cancer patients

Abstract: Several genes encoding different cytokines may play crucial roles in host susceptibility to lung cancer, since cytokine production capacity varies among individuals and depends on cytokine gene polymorphisms. The association between cytokine gene polymorphisms with primary lung carcinoma was investigated. DNA samples were obtained from a Turkish population of 44 patients with primary lung cancer, and 59 healthy control subjects. All genotyping (IFN-gamma, TGF-beta1, TNF-alpha, IL-6 and IL-10) experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 36 publications
4
29
1
7
Order By: Relevance
“…A significant association has been reported between IFN-g polymorphisms and cervical and pancreatic cancers (Halma et al, 2004;Gangwar et al, 2009), whereas no associations have been detected for breast, lung, and cervical cancers in particular populations (Halma et al, 2004;Gonullu et al, 2007;Colakogullari et al, 2008). Also, no significant associations were detected between allele/genotype frequencies and clinical parameters in our CML patient group.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A significant association has been reported between IFN-g polymorphisms and cervical and pancreatic cancers (Halma et al, 2004;Gangwar et al, 2009), whereas no associations have been detected for breast, lung, and cervical cancers in particular populations (Halma et al, 2004;Gonullu et al, 2007;Colakogullari et al, 2008). Also, no significant associations were detected between allele/genotype frequencies and clinical parameters in our CML patient group.…”
Section: Discussionmentioning
confidence: 49%
“…Also, there is no association between TNF-a and myeloma/myelodisplastic syndrome (Gyulai et al, 2005;Au et al, 2006). Although TNF-a polymorphism association in colorectal and NSCLC has been reported, there are no studies on the association between TNF-a polymorphisms and CML in the literature (Colakogullari et al, 2008;Wu et al, 2008). This is the first study in this field, and it was shown that TNF-a polymorphisms do not play a role in the prognosis of CML.…”
Section: Discussionmentioning
confidence: 99%
“…For the T+869C polymorphism, 5 relevant studies with a total number of 1167 cases and 1365 controls were included in the meta-analysis [23][24][25][26][27]. Of these studies, 3 were conducted on Asian populations, and 2 on Caucasian descendants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Em cada doença este processo irá atuar de uma forma, na DPOC esta resposta estará atrelada as vias aéreas e será de caráter anormal nos pulmões promovendo a obstrução (AZAMBUJA et al, 2013). Já no CP, o desequilíbrio de mediadores pró e anti-inflamatórios poderá afetar a oncogênese mediada pela inflamação (COLAKOGULLARI et al, 2008), enquanto na infecção causada pelo M. tuberculosis é o que promoverá a resposta inflamatória em pacientes com TB (SELVARAJ et al, 2008).…”
Section: Introductionunclassified
“…Muitos estudos sugerem que polimorfismos de nucleotídeo único (SNPs) em genes que codificam citocinas teriam relação à susceptibilidade a estas doenças pulmonares (COLAKOGULLARI et al, 2008;CÓRDOBA-LANÚS et al, 2011). Estes polimorfismos estariam influenciando a transcrição do gene, conduzindo a variações na produção de citocinas (HU et al, 2015).…”
Section: Introductionunclassified